Hepatic Ago2-mediated RNA silencing controls energy metabolism linked to AMPK activation and obesity-associated pathophysiology - Cai Zhang (Nature Portfolio, 2018)
The RNA-induced silencing complex (RISC) represses gene expression via micro-RNA guided mRNA silencing. Here, the authors show that RISC component Argonaute 2 in the liver regulates energy metabolism by inducing microRNAs that cause metabolic disruption and by suppressing protein translation linked to AMPK activation.